Aktivitas Anti-Acne Daun Turi (Sesbania grandiflora (L.) Poir.) terhadap Propionibacterium acne - Alvi Kusuma Wardani; Anna Pradiningsih; Nurul Qiyaam; Shah Iqbal Ikraman Akbar (JURNAL ILMU KEFARMASIAN INDONESIA, 2022)
Turi (Sesbania grandiflora (L.) Poir.) is a native Indonesian plant with many benefits. One of the benefits of Turi leaves is that they can be used as antibacterial agents. Turi leaves contain several compounds with antibacterial bioactivity including tannins, flavonoids, and saponins. This study aimed to examine the activity of Turi leaf extracts against Propionibacterium acne, a bacterium that causes acne. Antibacterial activity testing was performed using the good diffusion method with three replicates. The test groups were X1, X2, and X3, which had extract concentrations of 5%, 7.5%, and 10%, respectively. The positive control group was treated with clindamycin disks. The results of measurements of the diameter of the inhibition zone showed that the mean for groups X1, X2, and X3 were 19.67 mm, 22 mm, and 23.67 mm, respectively. The positive control group was 37 mm. Based on the classifi cation of bacterial growth inhibition responses, the results of the inhibition zone diameter after deducting the good diameter × 10 mm were classifi ed as less eff ective for group X1 and weak for groups X2 and X3. The positive control group was classifi ed as strong. This study concluded that the antiacne activity of Turi leaf extracts at a concentration of less than 10% was weak when compared to the positive control.